Drying kinetics, energy use, and functional quality of lemon slices in convective, microwave, and hybrid systems - Siabdallah, Nourelislam; Dahmoune, Farid; Himed-Idir, Hayat; Ferhat, Radhia; Renzo, Giovanni Carlo Di (Journal of Food Technology Research, 2026)
The present study investigated the drying behavior and quality attributes of lemon slices subjected to three drying techniques: convective drying (CD), microwave drying (MD), and combined microwave-convection drying (CMD). The major objectives were to assess drying kinetics, energy efficiency, and the preservation of functional quality. Parameters such as drying time, drying rate, effective moisture diffusivity, specific energy consumption, energy efficiency, color retention, and the stability of bioactive compounds were evaluated. Twenty-two mathematical models were fitted to the experimental data and evaluated using three statistical criteria (R², χ², and RMSE). The best-performing model provided the closest fit to the drying kinetics of lemon slices, with 0.9923 ≤ R² ≤ 0.9995, 3.90×10⁻⁵ ≤ χ² ≤ 6.21×10⁻⁴, and 5.99×10⁻³ ≤ RMSE ≤ 2.47×10⁻² across all drying conditions. CMD and MD reduced drying time by more than 80% compared to CD, while CMD increased the effective moisture diffusivity by approximately 70%. Specific energy consumption decreased by up to 60% under CMD and MD, with microwave drying at 900 W demonstrating the highest energy efficiency. CMD also ensured better retention of phenolic compounds and antioxidant activity, and it resulted in up to 50% less color degradation compared to CD. The integrated system enabled real-time monitoring of drying and moisture dynamics, facilitating accurate prediction of drying behavior and product quality. Overall, the study demonstrated that CMD offers an optimal balance between preserving product quality and enhancing drying efficiency, making it a scalable and sustainable solution for industrial lemon drying processes.